Metodological principles of student research activities in the context of professional training of lawyers - Череватюк, Вікторія Богданівна; Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article outlines the main directions of students research. Attention is focused on science club activities in various forms such as round tables, conferences, discussions etc. Founded out the result of this activity has become highly competitive training lawyers with an appropriate level of professional legal culture.